Complete mitochondrial genome of Buffon’s river garfish Zenarchopterus buffonis (Valenciennes, 1847) - Wei Tan; Jinye Liu; Yongbo Wang; Hongtao Liu; Hongji Ke; Jiawei Fan; Shuyuan Fu; Ming Luo; Longlong Liu; Fuxiao Chen; Yuxiang Zhang (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of Buffon’s river garfish Zenarchopterus buffonis from South China Sea has been obtained for the first time. It is 16,462 bp long, and contains 21 tRNA genes, 2 rRNA genes, 13 protein-coding genes (PCGs), and 1 control region. The overall base composition is significantly biased (A, G, T, and C was 33%, 12.94%, 29.78%, and 24.27%, respectively) with A + T contents of 62.79%. In total, most PCGs use the initiation codon ATG except COX1 uses GTG. Seven PCGs have a complete codon TAA or TAG, whereas the other six genes end with the incomplete stop codon T–– or TA–. Phylogenetic analysis showed that Z. buffonis forms a monophyletic cluster with the species of Belonidae, Zenarchopteridae, and Sconberesocidae.